Khoʻ nu cuṃ mha panʻʺ mu chuiʺ - Khyacʻ Kui Kui, Ūʺ, 1926- (Cā pe Bimānʻ thutʻ praññʻ sūʹ lakʻ cvai cā cañʻ, 1995)
Author's travel account while on a botanical excursion to Khoʻ nu cuṃ or Mount Victoria Region in Chin State, Burma.